RECLAIMING AUTHENTICITY WITHIN THE ATTENTION ECONOMY - Tiidenberg, Katrin; Kneas, David (AoIR Selected Papers of Internet Research, 2026)
The interplay between authenticity and attention is central to social media sociality, yet navigating this tension is complex. Previous research has explored how influencers and content creators perform authenticity, but our study focuses on everyday users, analyzing their experiences and strategies through a meta-analysis of ethnographic and interview data spanning 13 years. Our findings highlight three key dynamics. First, users experience an inherent tension between authenticity and attention, shaped by platform norms and community expectations. Even those who do not seek to capitalize on their popularity feel pressured to leverage the attention they generate, and negative perceptions of 'attention-seeking' seem to be broadly internalized. Second, users reaffirm authenticity through distinct registers of love, lifestyle, and greater good, strategically framing their socially mediated self-presentation to maintain a sense of authenticity while engaging with social media’s attention structures. Lastly, perceptions of platform affordances, in particular in terms of how attention is meant to circulate on platforms, shape how users navigate the tensions between attention and authenticity. Rather than a fixed ideal or a purely instrumental form of performance, social media authenticity emerges from this analysis as a flexible construct. This argument contributes to a nuanced understanding of how everyday users—not just influencers—navigate the complexities of digital self-presentation in an era where attention and authenticity remain in constant negotiation.